2021
DOI: 10.11604/pamj.2021.40.11.26681
|View full text |Cite
|
Sign up to set email alerts
|

Determining the level of condom use and associated factors among married people in Tshwane District of South Africa

Abstract: Introduction despite the wide availability of free male condoms in South Africa, high rates of new HIV transmissions are reported to occur among married couples. The aim of this study was to determine the level of condom use among the married people and to assess the factors associated with condom use in the Tshwane district of the Gauteng province. Methods a cross-sectional study was conducted among 325 clients accessing health care services at the Steve Biko Academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Consistent with our results, a recent study conducted among sexually active men in Nigeria 33 show that Open access knowledge of equally improved condom use. Another study conducted among South African married couples reported that females are less likely to use a condom if their male partner has refused to use a condom, 34 suggesting male dominance or power imbalance between women and men in condom negotiation. In our context, this finding could be explained by sociocultural differences between men and women, with the latter being inherently submissive to the sexual demands of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, a recent study conducted among sexually active men in Nigeria 33 show that Open access knowledge of equally improved condom use. Another study conducted among South African married couples reported that females are less likely to use a condom if their male partner has refused to use a condom, 34 suggesting male dominance or power imbalance between women and men in condom negotiation. In our context, this finding could be explained by sociocultural differences between men and women, with the latter being inherently submissive to the sexual demands of the latter.…”
Section: Discussionmentioning
confidence: 99%